Low Plasma Citrate Levels and Specific Transcriptional Signatures Associated with Quiescence of CD34+ Progenitors Predict Azacitidine Therapy Failure in MDS/AML Patients - Koralkova, Pavla; Belickova, Monika; Kundrat, David; Dostalova Merkerova, Michaela; Krejcik, Zdenek; Szikszai, Katarina; Kaisrlikova, Monika; Vesela, Jitka; Vyhlidalova, Pavla; Stetka, Jan; Hlavackova, Alzbeta; Suttnar, Jiri; et al. (Cancers, 2021)
To better understand the molecular basis of resistance to azacitidine (AZA) therapy in myelodysplastic syndromes (MDS) and acute myeloid leukemia with myelodysplasia-related changes (AML-MRC), we performed RNA sequencing on pre-treatment CD34+ hematopoietic stem/progenitor cells (HSPCs) isolated from 25 MDS/AML-MRC patients of the discovery cohort (10 AZA responders (RD), six stable disease, nine progressive disease (PD) during AZA therapy) and from eight controls. Eleven MDS/AML-MRC samples were also available for analysis of selected metabolites, along with 17 additional samples from an independent validation cohort. Except for two patients, the others did not carry isocitrate dehydrogenase (IDH)1/2 mutations. Transcriptional landscapes of the patients' HSPCs were comparable to those published previously, including decreased signatures of active cell cycling and DNA damage response in PD compared to RD and controls. In addition, PD-derived HSPCs revealed repressed markers of the tricarboxylic acid cycle, with IDH2 among the top 50 downregulated genes in PD compared to RD. Decreased citrate plasma levels, downregulated expression of the (ATP)-citrate lyase and other transcriptional/metabolic networks indicate metabolism-driven histone modifications in PD HSPCs. Observed histone deacetylation is consistent with transcription-nonpermissive chromatin configuration and quiescence of PD HSPCs. This study highlights the complexity of the molecular network underlying response/resistance to hypomethylating agents.